Assessment of antioxidant activity, amino acids, phenolic acids and functional attributes in defatted rice bran and rice bran protein concentrate - Zaky, Ahmed A.; Chen, Zhou; Qin, Ming; Wang, Meizi; Jia, Yingmin (Progress in Nutrition, 2021)
The antioxidant capacities, amino acid composition and phenolic acid profile of defatted rice bran (DRB) and rice bran protein concentrate (RBPC) were investigated. The functional attributes of DRB and RBPC were also evaluated. The obtained results showed that DRB and RBPC owned good antioxidant activities, which give DPPH of 56.56 and 48.17%, ABTS of 45.34 and 32.27%, and a metal chelating activity of 53.14 and 58.81%, respectively. Essential amino acids in RBPC displayed a greater abundance when compared to DRB, whereas DRB had higher individual phenolic acid contents than RBPC. Furthermore, the results showed that ferulic acid was released in the highest concentration between various phenolics followed by p-coumaric acid. Also, the obtained data exhibited that RBPC had good emulsifying activity and foaming capacity than DRB. Our results indicate that DRB could be useful as natural antioxidants and can be used as an inexpensive alternative to synthetic food additives. Additionally, rice bran protein concentrate has an excellent prospective as functional food which can be effective for future food applications.